1997
DOI: 10.1159/000262373
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Salivary Flow Rate and pH at the Surface of the Dentition following Consumption of Acidic Beverages

Abstract: Use of a splint-mounted flexible pH electrode has allowed reliable continuous monitoring of pH at the surface of the dentition whilst still enabling subjects to drink normally. pH was monitored at the palatal upper left central incisor and upper right first permanent molar sites after drinking 1% (w/v) citric acid. A maximal decrease in pH to values of 2–3 was observed after 1 min followed by a slower recovery which was above pH 5.5 within 2 min at the former site and in 4–5 min at the latter site. A sharp ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
1
14

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 3 publications
4
95
1
14
Order By: Relevance
“…The decreases in pH observed after drinking tea were minimal compared with those previously observed after drinking 1% citric acid (similar concentration to some fruit-based acidic drinks) where pHs as low as 2 were reached. 20 Not only were the pH decreases very small but also, they occurred very rapidly (maximal at 20 to 25 seconds) and resting pH levels were restored within approximately 2 minutes. Although there was a greater decrease in the incisor region compared with the molar region, this would not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decreases in pH observed after drinking tea were minimal compared with those previously observed after drinking 1% citric acid (similar concentration to some fruit-based acidic drinks) where pHs as low as 2 were reached. 20 Not only were the pH decreases very small but also, they occurred very rapidly (maximal at 20 to 25 seconds) and resting pH levels were restored within approximately 2 minutes. Although there was a greater decrease in the incisor region compared with the molar region, this would not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of black tea on tooth surface pH was assessed using an in situ pH monitoring approach previously reported by our group. 20 Essentially, this involved the manufacture of vinyl splints from individual alginate impressions and plaster casts of the subjects' maxillary dentition. Short lengths of small-bore plastic tubing were mounted on the splints at two positions with cold cure acrylic to provide mounting points for a micro-pH electrode (0.6 mm diameter).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow rate in the artificial mouth during erosion with citric acid was applied in order to mimic oral conditions during consumption of a beverage. 20 Since it was suggested that exposure to the acidic environment without salivary interaction should not exceed a period of 2 min/cycle, the specimens were subjected to 6 x 30 s of erosion daily. These in vitro conditions simulate intra-oral real-life conditions as closely as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between unstimulated salivary flow rate and buffering capacity with dental erosion have been reported (Hellström, 1977;Woltgens et al, 1985;Bevenius & l'Estrange, 1990;Järvinen et al, 1991;Gudmundsson et al, 1995), although such associations were not observed in patients with reflux disease (Meurman et al, 1994) or in a recent case-control study of children (Al-Dlaigan et al, 2002). Nevertheless, both salivary flow and buffering capacity appear to be important in neutralising dietary acid as demonstrated by the restoration of resting pH at the tooth surface within a few minutes of acid consumption (Millward et al, 1997). Considerable intersubject variation appears to exist in the ability to buffer acidic drinks, although intrasubject variation is less (McCay & Will, 1949).…”
Section: Dental Disease and Salivary Factorsmentioning
confidence: 97%